The black swan of American Presidency : comparing Obama and Trump's foreign policies on Southeast Asia - Desker, Reesa Corrie (2018)
Within the span of a decade, America has elected two successive presidents whose personalities and visions stand far apart on the leadership and political spectrum. Sworn into office in January 2017, President Donald Trump has hitherto made key changes to his predecessor President Barack Obama’s two-term (2009-2016) work in foreign policy that have had ripple effects worldwide. His campaign rhetoric and general temperament are a deviation from American presidents of the past and elicit the question of a new normal in U.S. government and foreign policy. With the passing of an unprecedented Golden Age of attention that Southeast Asia enjoyed under Obama, the challenge ahead is for the Trump administration to match this level of engagement. This paper compares the divergent political inclinations of both presidents amidst the circumstances surrounding their presidencies, in order to comprehend their intentions and actions in engaging with Southeast Asia, and specifically Singapore.